2020
DOI: 10.5194/acp-20-10845-2020
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol solar radiative forcing near the Taklimakan Desert based on radiative transfer and regional meteorological simulations during the Dust Aerosol Observation-Kashi campaign

Abstract: Abstract. The Taklimakan Desert is a main and continuous source of Asian dust particles causing significant direct radiative effects, which are commonly quantified by the aerosol solar radiative forcing (ASRF). To improve the accuracy of estimates of dust ASRF, the Dust Aerosol Observation-Kashi (DAO-K) campaign was carried out near the Taklimakan Desert in April 2019. The objective of the DAO-K campaign is to provide crucial parameters needed for the calculation of ASRF, such as dust optical and microphysical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 73 publications
(106 reference statements)
5
23
0
Order By: Relevance
“…The results indicated that the method is effective in estimating the SW DRFE dust over land. The microphysical properties of dust aerosols significantly influence the DRE dust and the DRFE dust (Che et al, 2012;Li et al, 2018). The different microphysical properties of dust aerosols in various dust source regions cause uncertainties in estimating the SW DRE dust and DRFE dust .…”
Section: The Equi-albedo Methodsmentioning
confidence: 99%
“…The results indicated that the method is effective in estimating the SW DRFE dust over land. The microphysical properties of dust aerosols significantly influence the DRE dust and the DRFE dust (Che et al, 2012;Li et al, 2018). The different microphysical properties of dust aerosols in various dust source regions cause uncertainties in estimating the SW DRE dust and DRFE dust .…”
Section: The Equi-albedo Methodsmentioning
confidence: 99%
“…According to the AOD calculation in WRF-Chem, we can either choose the aerosol number concentration (option 1) or aerosol mass concentration (option 2) as control variables. Li et al (2020) describes option 1. This study selects option 2 and describes it in the following subsections.…”
Section: Assimilation Systemmentioning
confidence: 99%
“…All the instruments were deployed at the roof of a three-story building on the campus. Please refer to Li et al (2020) for more details about the field campaign.…”
Section: Observational Data and Errorsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in previous researches, the atmospheric aerosol particles mainly exert cooling effects both at the top and bottom of the atmosphere (TOA and BOA) and an overall atmospheric warming effect of the entire atmospheric column (difference between TOA and BOA) on a long timescale [7,9]. However, the quantification of the aerosol radiative effects depends on aerosol loading, aerosol species (different microphysical and chemical properties), and is even susceptible to the surface properties, vertical structures of the atmosphere, and cloud conditions [10][11][12]. The local, instantaneous, and short-term (a few days to several months) quantities of aerosol radiative effects could differ dramatically (up to hundreds of W/m 2 ), even with dynamic warming or cooling effects, owing to the spatial and temporal variations of atmospheric aerosols and surrounding conditions [7,12].…”
Section: Introductionmentioning
confidence: 99%